2014
DOI: 10.1021/jf402735u
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of the Leaves of Loquat (Eriobotrya japonica) on Bone Mineral Density Loss in Ovariectomized Mice and Osteoclast Differentiation

Abstract: The loquat, Eriobotrya japonica Lindl. (Rosaceae), is a small tree native to Japan and China that is widely cultivated for its succulent fruit. Its leaves are used as an ingredient of a tasty tea called "Biwa cha" in Japanese. The anti-osteoporosis effects of the leaves of loquat in vitro and in vivo have been investigated. After 15 days of feeding normal diet or diet supplemented with 5% loquat leaves, the body weight, viscera weights, and bone mineral density (BMD) of both groups of eight ovariectomized (OVX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 20 publications
2
33
0
Order By: Relevance
“…Furthermore, they showed that the expression of osteoblast-specific genes was enhanced after UA treatment, and that UA could induce osteoblastogenesis and mineralization of osteoblasts in vitro, which was associated with the activation of MAPKs, activator protein-1 (AP-1), and NF-kB [12]. Further, Tan et al observed that UA extracted from loquat leaves inhibited bone mineral density loss in ovariectomized mice [13]. These findings suggest that UA may be valuable for the treatment of metabolic osteopathy characterized by bone mass loss.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they showed that the expression of osteoblast-specific genes was enhanced after UA treatment, and that UA could induce osteoblastogenesis and mineralization of osteoblasts in vitro, which was associated with the activation of MAPKs, activator protein-1 (AP-1), and NF-kB [12]. Further, Tan et al observed that UA extracted from loquat leaves inhibited bone mineral density loss in ovariectomized mice [13]. These findings suggest that UA may be valuable for the treatment of metabolic osteopathy characterized by bone mass loss.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, loquat leaves may ameliorate Alzheimer’s disease, since E. japonica leaves protect against oxidative stress and cognitive deficits induced by the Aβ peptide [13]. Our previous studies showed that E. japonica have the potential to suppress ovariectomy-induced bone mineral density deterioration [14], and isolated triterpenoids as the major bioactive compounds suppress osteoclast differentiation [15]. As a powerful indigenous therapy, loquat leaves have also been used for skin-care application such as for sunburn, dermatitis, and skin aging.…”
Section: Introductionmentioning
confidence: 99%
“…Ovariectomized mice have been classically used as animal models for simulating osteoporosis of postmenopausal women (Lee et al, ; Tan et al, ). Since there are no apparent symptoms in early‐stage of osteoporosis, BMD test has been regarded as an effective means to diagnose this disease (Seeman, ).…”
Section: Resultsmentioning
confidence: 99%